2022
DOI: 10.3389/fneur.2021.786734
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Functional Connectivity Signatures of MRgFUS Vim Thalamotomy in Parkinson's Disease: A Preliminary Study

Abstract: Magnetic Resonance-guided high-intensity Focused Ultrasound (MRgFUS) of the thalamic ventral intermediate nucleus (Vim) for tremor has increasingly gained interest as a new non-invasive alternative to standard neurosurgery. Resting state functional connectivity (rs-FC) correlates of MRgFUS have not been extensively investigated yet. A region of interest (ROI)-to-ROI rs-FC MRI “connectomic” analysis focusing on brain regions relevant for tremor was conducted on 15 tremor-dominant patients with Parkinson's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 111 publications
0
18
0
Order By: Relevance
“…Numerous studies have used imaging techniques to demonstrate the presence of structural and functional brain alterations in patients with TE and PD [ 8 , 9 , 10 ]. Some previous reports in the literature also explored the possible prognostic value of imaging finding, using standard and advanced imaging techniques, in patients submitted to pharmacological, surgical, and less invasive treatments for tremor [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have used imaging techniques to demonstrate the presence of structural and functional brain alterations in patients with TE and PD [ 8 , 9 , 10 ]. Some previous reports in the literature also explored the possible prognostic value of imaging finding, using standard and advanced imaging techniques, in patients submitted to pharmacological, surgical, and less invasive treatments for tremor [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study also found no significant change in the neural spontaneous activity of the Vim lesion site, while decreased in the left occipital cortex after MRgFUS thalamotomy [33]. The rs-fMRI study from Jang et al and Mario et al indicated a significant perturbation in the cortical network rather than the thalamus as well [4, 34]. This may be a manifestation of neuro-dynamics compensation or brain structure remodeling; another possible explanation for this phenomenon is that our 3T MRI-based imaging scans have relatively limited capabilities for subcortical tissue, restricting us to capture more subtle changes.…”
Section: Discussionmentioning
confidence: 94%
“…Local efficiency is defined by evaluating which of a node’s neighbors are neighbors of each other and is a measure of network segregation. The accumulation and dissemination of α-synuclein aggregates in the brain in the early stages of PD has been demonstrated to be associated with alterations in resting-state FC in the basal ganglia, intercortical, and intracortical networks ( Stanziano et al, 2021 ). It has also been demonstrated that brain structural and functional connections are damaged in the early stages of PD.…”
Section: Discussionmentioning
confidence: 99%